2013
DOI: 10.1016/j.electacta.2013.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic aspects of the electrocatalysis of acid reduction in organic solvent using molecular diiron-dithiolate compounds

Abstract: To cite this version:Francois Quentel, Frederic Gloaguen. Kinetic and thermodynamic aspects of the electrocatalysis of acid reduction in organic solvent using molecular diiron-dithiolate compounds. 2015. AbstractIn an attempt to obtain molecular H 2 production electrocatalysts achieving balanced basicity and reduction potential, we focused on the mono-substituted diiron-dithiolate derivative [Fe 2 (µ-bdt)(CO) 5 (P(OMe) 3 )] (bdt = benzenedithiolate). The electrocatalytic efficiency of this iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…One way out of these difficulties is to focus on the foot of the CV wave where the contributions of all side-phenomena are minimal. 25,26,42 Another way is to raise the scan rate so as to decrease the charge passed during the experiment and thus minimize all the side-phenomena. These two strategies may also be applied simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…One way out of these difficulties is to focus on the foot of the CV wave where the contributions of all side-phenomena are minimal. 25,26,42 Another way is to raise the scan rate so as to decrease the charge passed during the experiment and thus minimize all the side-phenomena. These two strategies may also be applied simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39] This approach has been well illustrated by [Fe 2 (m-bdt)(CO) 6 ] (1; bdt = benzenedithiolate; Scheme 1), which is an easily synthesized proton-reduction catalyst combining reversible reductive electrochemistry and good activity at mild potentials in organic solvents: E 1/2 = À1.30 V versus ferrocenium/ferrocene (Fc + /0 ) in MeCN. [40][41][42] Recently, we have demonstrated that complex 1 was still reduced at mild potentials in aqueous solutions [E 1/ Encouraged by these results, we reasoned that complex 1 included in SDS micelles could potentially be an efficient protonreduction catalyst for photocatalytic H 2 production in water. Herein we report the performance of a PGM-free system consisting of complex 1, EY 2À as a sensitizer, and triethylamine (Et 3 N) as a sacrificial electron donor in an aqueous SDS solution.…”
Section: Introductionmentioning
confidence: 99%
“…4 These observations do however support the earlier proposed hypothesis that the LUMO should be primarily metal centered, 38 explaining why [2] 6 is more active than [3] 10 (comparing the TOF). [39][40][41] It should be noted that the rigidity of these naphthalene systems, together with their stabilizing charge effect results in more stable reduced species compared to alkyl-thiolate linkers. 42…”
Section: S K-edge Xanesmentioning
confidence: 99%